Commercial Nile tilapia Oreochromis niloticus production in net cages at the River Dakatia, Chandpur, Bangladesh (Journal of Bangladesh Academy of Sciences, 2023)
This study examined the intensification of mono-sex Nile tilapia Oreochromis niloticus aquaculturein riverine net cages installed at the River Dakatia, Roghunathpur, Chandpur. This study performed 120-day cage grow-out trials with densities of 50, 75, and 100 tilapia m-3 under three replications with an average initial weight of 28.92±8.37 g per juvenile fish. The monthly water quality parameters (temperature, pH, dissolved oxygen, total alkalinity and hardness, ammonia-N and Nitrite-N) in the cage installation water area of the River Dakatia were found to be suitable for tilapia cage culture. The monthly average weight gain was significantly (p < 0.05) higher in 50 tilapia m-3 stocking density than in the other two stocking densities tested. The mean final weight and specific growth rate were significantly (p < 0.05) higher in 50 tilapia m-3 stocking density than the other two stocking densities. Significantly (p < 0.05) higher survival (97.92%) was found in the 50 tilapia m-3 stocking density group and followed by 86.74% and 84.39% in the 75 and 100 tilapia m-3 stocking densities, respectively. Consequently, the monthly relative and specific growth rate and feed conversion ratio were significantly (p < 0.05) higher in 50 tilapia m-3 stocking density fishes for the first, third, and fourth months. Gross production was comparable between 50 and 75 tilapia m-3 stocking densities but was significantly (p < 0.05) better than 100 m-3 stocking density. Net production was significantly (p < 0.05) higher at 50 tilapia m-3 stocking density group than those of 75 and 100 tilapia m-3 stocking densities. The best feed conversion ratio (1.60) was in the 50 tilapia m-3 stocking density group (p < 0.05) than those of 1.87 and 2.44 for the stocking of 75 and 100 tilapia m-3, respectively. Benefit-cost ratio and net profit were significantly (p < 0.05) better at 50 and 75 tilapia m-3 than at 100 tilapia m-3 stocking density. Therefore, considering maximum outputs, benefits, and performances, we recommend stocking density at 50 mono-sex tilapia m-3 for the best growth, cost-effective production, and highest-economic return from 120 days of grow-out net cages in the riverine culture system.J. Bangladesh Acad. Sci. 47(1); 43-52: June 2023